2015
DOI: 10.1002/14651858.cd011306.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Stopping long-acting beta2-agonists (LABA) for adults with asthma well controlled by LABA and inhaled corticosteroids

Abstract: This review suggests that stopping LABA in adults who have stable asthma while they are taking a combination of LABA and ICS inhalers may increase the likelihood of asthma exacerbations that require treatment with oral corticosteroids, but this is not certain. Stopping LABA may slightly reduce asthma control and quality of life, but evidence was insufficient to show whether this had an effect on important outcomes such as serious adverse events and exacerbations requiring hospital admission, and longer trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…We do not know whether patients discontinued LABA because they had achieved good control over their asthma symptoms or for other reasons. For confirmation of appropriate step-down therapy, more granular clinical data (e.g., symptoms and pulmonary function and safety outcomes) and careful evaluation of long-term stability are needed; 18 21 however, these data were not available in this current US claims database.…”
Section: Discussionmentioning
confidence: 99%
“…We do not know whether patients discontinued LABA because they had achieved good control over their asthma symptoms or for other reasons. For confirmation of appropriate step-down therapy, more granular clinical data (e.g., symptoms and pulmonary function and safety outcomes) and careful evaluation of long-term stability are needed; 18 21 however, these data were not available in this current US claims database.…”
Section: Discussionmentioning
confidence: 99%
“…Two Cochrane reviews found insufficient trial evidence regarding step down of ICS or long-acting beta agonists (LABA). 16 , 17 Participants in our study used a variety of approaches to step down, reducing both ICS and LABA or just ICS; with even less concord for patients with an additional asthma therapy. Moreover, there was no consensus as to how to identify suitable patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility for adjusting the controller medication would be to eliminate the LABA from the combination, returning to the use of ICS therapy alone. However, a meta-analysis of studies involving adults (59) showed that the elimination of the LABA leads to a reduction in the quality of life and in asthma control. A subanalysis of a recent RCT (45) comparing the ICS+LABA combination with ICS alone showed that, in patients with asthma that was well controlled with ICS+LABA, the shift to ICS alone significantly increased the risk of exacerbations.…”
Section: Control-based Asthma Management In Stepsmentioning
confidence: 99%